2001
DOI: 10.1046/j.0007-1323.2001.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of lymph node dissection during resection of intrahepatic cholangiocarcinoma

Abstract: Lymph node metastases were seldom limited to the regional lymph nodes; most tumour recurrence occurred in the liver. Lymph node dissection did not appear to improve patient survival. Lymph node dissection alone is not likely to improve the prognosis without further control of liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 20 publications
12
149
5
1
Order By: Relevance
“…In our 81 patients with lymph node recurrence, regional lymph node recurrence occurred in 13 patients only (16%). Therefore, we propose that aggressive and routine lymph node dissection in patients with ICC cannot always contribute to prevention of lymph node recurrence after operation 15, 16…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our 81 patients with lymph node recurrence, regional lymph node recurrence occurred in 13 patients only (16%). Therefore, we propose that aggressive and routine lymph node dissection in patients with ICC cannot always contribute to prevention of lymph node recurrence after operation 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…Details of our surgical techniques and patient follow‐up methods have been reported previously 15, 16, 17. Major hepatectomies with bile duct resection were carried out when bile duct invasion of ICC was suspected to affect the first branch of the hepatic duct.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to gallbladder and pancreatic adenocarcinomas, patients are often diagnosed late in the disease process with both nodal and distant metastases occurring early and often. [1][2][3][4][5][6][7][8] Among the minority of patients whose presentation is amenable to curative resection, local recurrence is the rule not the exception. 1,[9][10][11] While the only curative treatment for CC patients remains surgical resection, post-operative outcomes have shown no significant improvements in the past several years 11 with the current five-year survival rate stagnating at a mere 5% for all CC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Many surgeons have advocated aggressive surgery, including major hepatectomy, extended lymph node (LN) dissection and combined vascular resection for improving surgical outcomes (2-8). However, despite aggressive liver surgery, the prognosis after surgery remains unsatisfactory, with 5-year survival rates of 19-35% for HC (5-8), 32-53% for GBC (9-11) and 23-29% for IHCC (12)(13)(14). Moreover, several investigators have indicated that LN metastasis, intrahepatic metastasis and positive surgical margins in the bile duct are poor prognostic factors (12-15).…”
mentioning
confidence: 99%